Extreme rainfall events alter the trophic structure in bromeliad tanks across the Neotropics - Gustavo Q. Romero (Nature Portfolio, 2020)
The amount and frequency of rainfall structures aquatic food webs. Here the authors show that in tropical tank bromeliads, lower trophic levels are more abundant in stable rainfall conditions, while biomass pyramids are inverted in conditions with periodic droughts.